É preciso ter-ato: integração escola, família e comunidade pelo teatro do oprimido - RODRIGUES, Marcos André Gomes (2023)
The present text is the result of research developed in the project it is necessary to have-act: school, family and community integration through the Theater of the Oppressed, together with the Professional Master in Arts (PROFARTES/UFMA), it presents the pedagogical investigation on the need for theater in high school in a formal school, using the methodology of Theater of the Oppressed by Augusto Boal. The research locus is the Professor Antônio Carlos Beckman Teaching Center located in the municipality of Açailândia Maranhão, whose the trajectory of studies with students of the 1st, 2nd and 3rd years of high school was developed, whose objective is to understand the potential of the Theater of the Oppressed as a methodological approach for teaching theater at school in view of the students' reality, in addition to instigating reflections on the social issues experienced by students through the practice of TO and their relationship with the community in which they live as well as, promoting school, family and community integration through more of the themes presented and discussed through theatrical plays. In this way, it became essential to use as the main theoretical bases of this study the assumptions of authors like: Augusto Boal (1977, 1991, 1996, 1999, 2008, 2013 e 2014), creator of TO and Santana (2013), Olga Reverbel (1989), Koudela (2010), Desgranges (2011) among others who have helped the discussions raised here with the use of participant observation procedures in the scientific methodology has contemplated the action research. In this sense, the data collection techniques used were journal entries in order to highlight what was relevant in the research. In addition to the observation, semi-structured interviews and conversation circles were carried out, which has allowed us to understand the importance of the Theater of the Oppressed in the integration between school, family and community. Thus, the first chapter highlights the affirmative policies that throughout history have guaranteed the presence of theater in formal education. The second chapter highlights the potential of the Theater of the Oppressed in the school environment, presenting studies that were successful in the teaching and learning process through the techniques proposed by Boal. The third chapter brings the results and discussions of the research and the observation of the importance of TO in the sense of promoting school, family and community integration. From the results obtained in this study, it was verified the contributions of theater in the classroom and that the practices of Theater of the Oppressed have the potential to provide students with a re-signification of their socio-political conflicts, making the school a space for discussion among students, the family and the community.